Maasai Voices on Climate Change (and other changes, too). Documentary screening and Q&A session - Roque de Pinho, Joana (“Arid Lands: Environmental and Social Sustainability” International Conference, 2018)
https://vimeo.com/73980798 “Arid Lands: Environmental and Social Sustainability” International Conference, Al-Farabi KazNU Library. Al-Farabi Kazakh National University & The School of Geography and the Environment (University of Oxford), Almaty, Kazakhstan (April 11-12, 2018).